Luminescence dating of a sedimentary sequence in the eastern North Yellow Sea. (April 2022) - Gao, Lei; Li, Jun; Hu, Bangqi; Yi, Liang; Tamura, Toru; Long, Hao
Abstract: Sediments from the Yellow Sea (YS) are important archives for investigating the stratigraphic evolution in relation to global and regional sea-level changes. Here, the upper 40-m-thick interval of a 100-m-long drill core (NYS17), retrieved from the eastern North Yellow Sea (NYS), were studied to explore the late Quaternary sedimentary history in this region. To obtain reliable chronological framework of the core, we utilized multiple luminescence signals from sediments for dating. Coarse-grained (CG) and fine-grained (FG) quartz optically stimulated luminescence (OSL), and K-feldspar/polymineral post-infrared (IR) IR stimulated luminescence (pIRIR50/150 ) signals were analyzed to obtain age estimates for comparison. Primary results show that quartz OSL ages are consistent with the corrected ages of IR50 and pIRIR150 signals. Chronostratigraphy of core NYS17 presents two phases of rapid accumulation. One is at the interval of 35.6–29.8 m deep, as age controls of sedimentary stratigraphy are in the period of 135–130 ka, corresponding to Marine Isotope Stage (MIS) 6/5. Another occurs in the upper section (14.5–0.9 m) as luminescence ages are constrained between 11 and 9 ka. However, the overlying deposits after 9 ka seem to be very thin in the core site. This is likely attributed to the abundant terrestrial sediment supply during the early Holocene and following starvation after further rise of the sea level and transgression. In contrast, the MIS 5–2 interval remains far to be exactly defined in the core as no age constraint is available. Regionally, correlations of chronostratigraphy of our core with other collected cores from the YS and East China Sea, show comparable depositional records for both the late Pleistocene and Holocene sedimentary successions. These findings indicate that the spatiotemporal variations of sedimentary processes in the YS shelf were closely linked to global sea-level changes during the glacial-interglacial cycles. Highlights: We provide a new 135-ka-long chronological sequence for the upper 40-m-thick interval of a 100-m-long drill core (NYS17) in the eastern NYS. The reliability of the new chronology was examined by internal cross-check of ages from multiple luminescence signals and external chronostratigraphy in the YS. Two phases of rapid accumulation in 135–130 ka and 11–9 ka, associated with the inferred MIS5-2 stratigraphy are controlled by the sea-level changes.